Political Connection, Gender Diversification, and Firm Performance: The Moderating Role of Good Corporate Governance - Sari, Yovita; Mulya, Ali Sandy (Universitas Negeri Semarang, 2025)
Purpose: The research examines the influence of political connections and gender diversification on firm performance, with good corporate governance as a moderating variable. The research focuses on infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. Method: The research method used is Structural Equation Modeling - Partial Least Square (SEM-PLS) using WarpPLS Version 7.0 software. The population for this study is infrastructure sector companies listed on the Indonesia Stock Exchange in 2019-2022. This research used a non-probability purposive sampling technique, resulting in a total sample of 35 companies. Findings: The research results show that political connections do not affect firm performance. However, political connections on firm performance have a significant influence when moderated by good corporate governance. Gender diversification does not influence firm performance and good corporate governance cannot moderate the influence of gender diversification on firm performance. Novelty: Unlike prior research which focuses on sectors like banking and manufacturing, this study targets the infrastructure sector—strategic, politically linked, and historically male-dominated—making the discussion on gender diversity particularly relevant. The finding that GCG selectively moderates only political connections offers a novel contribution to existing literature.